Kegiatan “Rumah Belajar” Sebagai Media Menganalisis Perilaku Keluarga dengan Risiko Kejadian Balita Stunting - NLP Yunianti Suntari C; I Ketut Gama (Jurnal Kesehatan, 2020)
The rate of stunting or dwarf or acute malnutrition in children aged 1000 days in Indonesia is stagnant, which is around 37% of births from 2007 to 2013 (World Bank Report: Aiming High and Riskesdas, 2013). Children who are stunted will be more susceptible to illness and experience a decline in cognitive abilities that impact on the child's economic abilities in the future. Family development and empowerment is part of sensitive nutrition interventions. In carrying out its function role, the family has views and beliefs which will certainly affect the way the family takes care of children. This family paradigm is a basic belief held by the family, and guides actions in caring for and caring for their children. The "Rumah Belajar" activity guide for researchers developed into a joint study guide that families can do as a medium to analyze risky behavior in families with stunting toddlers in Singakerta Village, Ubud. This research uses quasi-experiment design. 66 families as a control group and 72 families as a treatment group. Samples are taken randomly from the number of banjar/posyandu available. Test the difference in the average of two sample pairs, before and after the "Rumah Belajar" activity in the treatment group. The results of the correlation before and after the "Rumah Belajar" in the treatment group showed a .866 figure with a probability value (sig) of .000. This means that family risk behavior is significantly related. Based on the comparison of the probability value (sig) .000 <0.05, then Ha is accepted that there are significant differences in family risk behavior before and after the "Rumah Belajar" activity.